Faktor - Faktor yang Mempengaruhi Komitmen Dokter di Puskesmas untuk Tidak Merujuk Kasus Non-Spesialistik Pasien BPJS di Kota Semarang - Hendro Sucipto; Chriswardani Suryawati; Sutopo Patria Jati (Jurnal Manajemen Kesehatan Indonesia, 2019)
Patients who should be able to be treated at the health center (puskesmas) but because of some matters referred to and handled in a hospital, it is a waste of health costs. Hence, BPJS will pay more according to INA CBG's tariff. 3       Advanced Health Facilities, in this case a hospital, is also object to having to deal with non-specialist cases, while the case can actually be completed at the first health facility. Handling non-specialist cases in hospitals leads to health services being less well targeted. The hospital will be very busy handling patients who are not supposed to, while patients who really need treatment in the hospital can be neglected. 2       This study aims to analyze factors which influence the commitment of doctors not to refer to non-specialist cases in health centers in the city of Semarang       The study was conducted with a cross sectional quantitative research design. The data were collected by calculating the total results of the questionnaire measurements on each variable with a Likert scale on 73 doctors in 37 health centers spread across the city of Semarang. The study was conducted during March to May 2018.       The results showed that the number of non-specialist cases of BPJS Health participant patients was still relatively high. This has to do with the commitment of doctors at the health center not to refer to non-specialist cases. The most influence factor to the commitment of doctors not to refer to non-specialist cases was the doctor's perception of the completeness of facilities and infrastructure and the doctor's perception of his competence